PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DAYA TARIK WISATA TIRTHA EMPUL DI DESA MANUKAYA LET, KECAMATAN TAMPAKSIRING, KABUPATEN GIANYAR - Ni Gusti Ayu Kartika (UHN IGB Sugriwa Denpasar, 2021)
The era of regional autonomy as an implication of the enactment of Law no. 32 of 2004, provides opportunities for each Regency/City Government to plan and manage their own regional development, as well as demands for active community participation in the development process from planning, implementation, monitoring and evaluation. The community as the main component in the development of community-based tourism has an important role in supporting the development of regional tourism which is aimed at developing local potential that comes from nature, socio-culture or the community's economy. Law No. 9 of 1990 concerning Tourism states that the community has the same and widest opportunity to participate in the implementation of tourism. Community participation in maintaining the natural and cultural resources owned is a big contribution and has the potential to become a tourist attraction. The local community of Manukaya Let Traditional Village, Tampaksiring District, Gianyar Regency plays an important role in planning and developing heritage tourism at Tirta Empul Temple. the involvement of local communities in tourism activities at Tirta Empul Temple does not provide direct economic benefits to all local communities involved in tourism operations to support their families' lives because they are still carrying out their respective professions as farmers, breeders, traders and employees or other employees to meet their needs. daily.